2016
DOI: 10.1007/s40030-016-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Effective Parameters on Drivers’ Attention Level to Urban Traffic Signs

Abstract: Traffic signs are one of the oldest safety and traffic control equipments. Drivers' reaction to installed signs is an important issue that could be studied using statistical models developed for target groups. There are 527 questionnaires have been filled up randomly in 45 days, some by drivers passing two northern cities of Iran and some by e-mail. Therefore, minimum sample size of 384 is fulfilled. In addition, Cronbach Alpha of more than 90 % verifies the questionnaire's validity. Ordinal logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[26,27] erefore, driving speed can to some extent reflect the rationality of the setting of exit advance guide signs in a highway tunnel. Kazemi et al [28] conducted 527 questionnaires that were filled up randomly in 45 days and found that driving speed, accidents in the last five years, occupation, driving time, and the number of accidents per day are the most important ones for the drivers. Malin and Luoma [29] evaluated the short-and long-term effects of speed display signs on driving speed at pedestrian crossings in a low-speed (40 km/h) urban environment.…”
Section: Effects Of Traffic Signs On Passenger Car Speedmentioning
confidence: 99%
“…[26,27] erefore, driving speed can to some extent reflect the rationality of the setting of exit advance guide signs in a highway tunnel. Kazemi et al [28] conducted 527 questionnaires that were filled up randomly in 45 days and found that driving speed, accidents in the last five years, occupation, driving time, and the number of accidents per day are the most important ones for the drivers. Malin and Luoma [29] evaluated the short-and long-term effects of speed display signs on driving speed at pedestrian crossings in a low-speed (40 km/h) urban environment.…”
Section: Effects Of Traffic Signs On Passenger Car Speedmentioning
confidence: 99%